Reprodutibilidade da tonometria arterial periférica para avaliação da função endotelial em adultos - Luisa Campos Caldeira Brant (2011)
Background: Endothelial dysfunction is associated to cardiovascular risk factors and predicts cardiovascular events. Peripheral arterial tonometry (PAT) is a new non-invasive method to assess endothelial function although there is a paucity of data about its reproducibility. Objectives: To evaluate the feasibility and the intraobserver reproducibility of PAT in adults. Methods: PAT exams were performed twice in the same day in 123 participants of a cohort about the determinants of diabetes and cardiovascular diseases (Brazilian Longitudinal Study of Adult Health ELSA). Endothelial function in PAT method is measured by reactive hyperemia index (RHI) which evaluates the changes in pulse wave amplitude in response to hyperemia. Agreement of RHI values was compared by Bland-Altman method and coefficient of variation. Reliability was assessed by intraclass correlation coefficient (ICC). Results: Mean values of RHI did not differ significantly between the exams of each participant (1,92±0,56 vs. 1,96±0,58, p=0,48). There were no systematic errors between the exams (mean of differences = -0,03±0,5). Measurement error was 0,35, coefficient of variation was 25,8% and ICC was 0,76. Gender, age or the presence of obesity did not influence the reproducibility of PAT. Conclusions: PAT exam is feasible and reproducible in adults. Reliability of PAT evaluated by ICC was considered very good, suggesting its utility in studies with discriminative purposes. Agreement of PAT measurements was found acceptable when compared to other non-invasive methods of endothelial function. This performance makes PAT a promising method to detect endothelial function in clinical and epidemiological studies